A taxonomic overview of Orchis sect. Robustocalcare (Orchidaceae) - Calevo, Jacopo; Christenhusz, Maarten J. M.; Fay, Michael F. (Phytotaxa, 2023)
Orchis patens has previously been considered to consist of three widely disjunct populations in northern Italy, Algeria/Tunisia and the Canary Islands. The last is already commonly treated as O. canariensis, but because the type of O. patens is from the Algerian populations, the name of the Italian taxon has been in doubt. We here review the taxonomic literature and provide a key to the species of O. section Robustocalcare supported by molecular data recently published for these three taxa. We conclude that Orchis patens subsp. brevicornis is the correct name for the Italian taxon.